Exploring Pain Diagnosis Patterns and Their Associated Causes in Anápolis, Goiás. (CIPEEX, 2026)
Introduction: Pain is a subjective and multifactorial experience that compromises quality of life and represents a challenge for healthcare systems, especially in its chronic form, which is recognized as a public health problem. In Brazil, its prevalence ranges from 39% to 76%, with significant social and economic impacts.Objective: To investigate pain diagnoses and possible associated conditions in hospital admissions, and to assess the profile of pain-related diagnoses that result in long-term hospitalizations recorded in Anápolis-GO during the year 2022.Methodology: A quantitative, descriptive study based on secondary data obtained from DataSUS through the TabWin software. Only Hospital Admission Authorizations (AIHs) issued in 2022 with ICD-10 codes related to pain were analyzed, excluding records from other periods or different locations. The variables included demographic characteristics, type and nature of admission, costs, and length of hospital stay.Results: No entries were found in the “associated ICD” field for hospitalizations due to pain, which prevented the analysis of comorbidities. Among the identified diagnoses, F06 (“Other mental disorders due to brain damage and dysfunction and to physical disease”) showed the highest number of prolonged hospitalizations (>45 days), with 19 cases, predominantly male (73.7%).Conclusion: The study identified weaknesses in the completeness of SIH/SUS data for pain-related cases, reinforcing the importance of training, audits, and standardized records. Furthermore, it highlights the need for integrated care strategies capable of providing multiprofessional support and reducing prolonged hospitalizations.
Keywords: Chronic pain; Hospital admissions; Information quality; Health management